Sensitivity Analysis for Effect of Changes in Input Data on Hydrological Parameters and Water Balance Components in the Catchment Area of Hungarian Lowland - Tran, Hop Quang (Journal of Environmental Geography, 2021)
Extreme weather and climate changes are emerging more frequently in Central Europe, Hungary, and in the near future the increase in prolonged droughts, high-intensity precipitation events and the temporal variations of precipitation are expected, which may increase the magnitude of local water damages (OVF, 2016). As a result of climate change, these extreme weather events will be more frequent, however it is difficult to predict them, as until now insufficient amount of observations are available on smaller watercourses and on refined territorial water balances. For the future assessment of the environmental and economic impacts of climate change, it is essential to explore the integrated relationship of evapotranspiration, runoff, infiltration, surface and subsurface waters, and other hydrological processes, which can fundamentally describe regionally the water management conditions. In this research, an earlier study (DHI Hungary 2019) on the catchment area of the main canal of the Dong-ér Brook is pursued to continue the development of the MIKE SHE model in a more complex manner. Within the frame of the present study, the relationship between the individual hydrological parameters, the water balance components and extreme precipitation events (drought, heavy rainfall events) for the entire drainage basin have been examined, besides, the expected effects of the predicted temperature rise on the water balance is evaluated. Using data from 2018 as reference, the sensitivity of the changes in daily precipitation and daily mean temperature has been assessed to estimate the effects of the future climate change on hydrological parameters and water balance components.